THE MEANING OF HEALING ACCORDING TO COUNSELES EXPERIENCING DRUG ADDICTION (Qualitative Study with Narrative Inquiry Design on Children in Foster Care at Inabah Toriqoh Pamijahan) - Satria Guruh Takbir Gumelar; Muhammad Muhajirin; Agung Nugraha (RADJA PUBLIKA, 2026)
Drug abuse not only causes physical impacts, but also results in psychological, social, and spiritual disorders that affect the sustainability of the recovery process. This study aims to understand the meaning of healing in individuals with a history of drug addiction while undergoing spiritual guidance at Inabah Toriqoh Pamijahan. The study used a qualitative approach with a Narrative Inquiry design . Participants were selected using a purposive sampling technique , namely foster children who have a history of drug addiction, are willing to participate in the study, and are able to tell their recovery experiences narratively. Data were collected through semi-structured interviews and observations, then analyzed using narrative analysis through the process of organizing data, restorying , interpreting meaning, and compiling narratives of participant experiences. The research findings identified four main themes, namely (1) life before recovery characterized by loss of direction and negative environmental influences, (2) the journey into spiritual recovery through the emergence of awareness and the decision to change, (3) transformation of awareness through the practice of Tawajuh which helps build inner peace, emotional regulation, self-awareness, and meaningfulness of life, and (4) Talqin as a reinforcement of spiritual recovery that strengthens commitment, self-control, and the sustainability of the recovery process. The research findings indicate that healing is interpreted as a process of identity reconstruction that is not only oriented towards stopping drug use, but also towards establishing the meaning of life, a closer relationship with Allah SWT, and the formation of a new spiritual identity. This research provides implications for the development of psychospiritual-based guidance and counseling services and serves as a basis for further research to test the effectiveness of the Tawajuh method as an intervention in the recovery of individuals with a history of drug addiction.